2017
DOI: 10.1021/acs.energyfuels.7b01973
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Mercury Removal Efficiency by Activated Carbon Treated with Nonthermal Plasma in Different Atmospheres

Abstract: To enhance the performance of activated carbon (AC) for elemental mercury removal, a kind of AC was modified by nonthermal plasma (NTP) and the effects of the modification of the atmosphere (N2, O2, air, and HCl) were investigated by adsorption and desorption experiments. The physical and chemical properties of original and modified ACs were characterized by Brunauer–Emmett–Teller, scanning electron microscopy with energy-dispersive spectroscopy, and X-ray photoelectron spectroscopy (XPS). The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…It is also found that the content of carbon species varies with the process parameters. It is speculated that some old chemical bonds may be broken and form new chemical bonds due to mechanical force on FA during ball milling. , Studies have shown that CO and COOH/C­(O)OC have a greater promoting effect on mercury removal performance . It is due to the fact that carbonyl and carboxyl/ester groups can increase the number of active sites on the adsorbent surface .…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is also found that the content of carbon species varies with the process parameters. It is speculated that some old chemical bonds may be broken and form new chemical bonds due to mechanical force on FA during ball milling. , Studies have shown that CO and COOH/C­(O)OC have a greater promoting effect on mercury removal performance . It is due to the fact that carbonyl and carboxyl/ester groups can increase the number of active sites on the adsorbent surface .…”
Section: Results and Discussionmentioning
confidence: 99%
“…As a result, the proportions of the different oxygen groups on the surface change by nonthermal plasma treatment. Moreover, porous carbon can be quickly functionalized by the nonthermal plasma within tens of seconds, which is obviously faster than that of activated carbon. …”
Section: Resultsmentioning
confidence: 99%
“…Mercury emission has brought widespread concern around the world due to its toxicity, , which can result in serious damage both on human health and ecosystem . Mercury release from coal-fired flue gas is taken as the largest anthropogenic emission source, , comprising 45% of the total amount . Because of its volatility, mercury easily migrates during the coal combustion process .…”
Section: Introductionmentioning
confidence: 99%